Ulnar variance in normal Nepalese population - Sharma, Sandeep; Sharma, Rajeeve; Neupane, Shankar; Subedi, Sonika (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: There are many factors that influence the ulnar variance such as age, sex, genetic factors, gross elbow pathology, gripping of the hand, rotation of the forearm and positioning of the elbow. There are several pathologies of the wrist in which ulnar variance play a role. We lack study in Nepalese population regarding the influence of age and sex on ulnar variance. The primary objective of this study was to determine the mean ulnar variance in normal Nepalese population and to assess age and sex difference. Material and Methods: This prospective study was conducted in Janaki Medical College and Teaching Hospital from July 2020 to March 2021. Total 120 patients were included in the study. Ulnar variance was measured by using the method of perpendiculars. Results: The mean value of ulnar variance was 0.73±1.62 in our population. In our study, thirty two (26.7%) had neutral ulnar variance, twenty two (18.3%) had negative ulnar variance and sixty six (55%) had positive ulnar variance. Conclusion: There was statistically significant difference in ulnar variance between male and female population (p<0.05). Females had higher ulnar variance than male population. There was more positive ulnar variance with higher age group (p<0.05).